Pengaruh Nilai Tukar dan Inflasi Terhadap Return Saham (Studi Kasus pada Perusahaan Retail) - Muhammad Nur Abdi; Agusdiwana Suarni; Diki Agusnawan (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study is a quantitative study to understand the effect of exchange rates and inflation on stock returns of retail companies listed on the Indonesia Stock Exchange between 2018 and 2020. The population of this study were 26 retail companies listed on the Indonesia Stock Exchange. By using purposive sampling so that the sample for this study is 6 retail companies listed on the Indonesia Stock Exchange during the 2018-2020 period. The type of data used in this research is quantitative data. In this study, the processed data is official data which is accessed through the IDX's official website (www.idx.co.id). The results show that, by applying the Statistical Package For the Social Science (SPSS) version 26, regarding the impact of exchange rates and inflation on stock returns of retail companies listed on the Indonesia Stock Exchange, using statistically calculated data, the authors conclude that the exchange rate has a negative and significant effect on stock returns of retail companies listed on the Indonesia Stock Exchange. Inflation has no significant positive effect on stock returns of retail companies listed on the Indonesia Stock Exchange.